The Role of Asiatic Acid in Preventing Dental Pulp Inflammation: An in-vivo Study - Nurhapsari A; Cilmiaty R; Prayitno A; Purwanto B; Soetrisno S (Dove Medical Press, 2023)
Arlina Nurhapsari,1,2 Risya Cilmiaty,3 Adi Prayitno,3 Bambang Purwanto,4 Soetrisno Soetrisno5 1Doctoral Degree of Medical Science, Faculty of Medicine, Sebelas Maret University, Surakarta, Central Java, Indonesia; 2Department of Conservative Dentistry, Faculty of Dentistry, Islam Sultan Agung University, Semarang, Central Java, Indonesia; 3Department of Oral Disease, Faculty of Medicine, Sebelas Maret University, Surakarta, Central Java, Indonesia; 4Department of Internal Medicine, Faculty of Medicine, Sebelas Maret University, Surakarta, Central Java, Indonesia; 5Department of Obstetrics and Gynaecology, Faculty of Medicine, Sebelas Maret University, Surakarta, Central Java, IndonesiaCorrespondence: Arlina Nurhapsari, Department of Conservative Dentistry, Faculty of Dentistry, Islam Sultan Agung University, Semarang, Jawa Tengah, 50112, Indonesia, Email arlina@unissula.ac.idPurpose: Acute dental pulp inflammation necessitates early treatment to alleviate inflammation and pain. In the inflammatory phase, a substance is required to lower the inflammatory mediators and reactive oxygen species that play a crucial role in that phase. Asiatic acid is a natural triterpene obtained from the Centella asiatica plant with a high antioxidant value. This study examined the effect of Asiatic acid's antioxidant, anti-inflammatory, and antinociceptive properties on dental pulp inflammation.Methods: The research is an experimental laboratory, with a post-test only with a control group design. The study utilised 40 male Wistar rats weighing 200- 250 grams and aged 8- 10 weeks. Rats were divided into five groups (control, eugenol, Asiatic Acid 0.5%; 1%; 2% group). Dental pulp inflammation was created in the maxillary incisor after six hours of administration of lipopolysaccharides (LPS). The dental pulp treatment then continued with the administration of eugenol and three different Asiatic acid concentrations (0.5%, 1% and 2%). In the next 72 hours, the teeth were biopsied, and the dental pulp was analysed using the enzyme-linked immunosorbent assay (ELISA) to measure the level of MDA, SOD, TNF-α, beta-endorphins and CGRP. Histopathological examination and the Rat Grimace Scale were utilised to determine the level of inflammation and pain, respectively.Results: The effect of Asiatic Acid on MDA, TNF-α, and CGRP levels decreased significantly compared to the control group (p=< 0.001). On the SOD and beta-endorphin levels, Asiatic acid treatment resulted in a considerable rise (p =< 0.001).Conclusion: Due to its antioxidant, anti-inflammatory, and antinociceptive characteristics, Asiatic acid can reduce inflammation and pain in acute pulp inflammation due to its ability to decrease MDA, TNFα, and CGRP levels while raising SOD and beta-endorphin levels.Keywords: pulp inflammation, Asiatic acid, MDA, TNF-α, SOD, beta endorphins, CGRP